Informativeness of phosphatidylethanol homologues as markers of alcohol consumption - E. V. Belyaeva; A. N. Karacheva; T. A. Bairova; N. V. Semenova; A. V. Belskikh; A. Yu. Marianian; E. A. Novikova; O. A. Nikitina; A. Yu. Sambyalova; O. A. Ershova; N. V. Nemchinova; D. P. Tiumentceva; et al. (Acta Biomedica Scientifica, 2025)
Background. Prenatal alcohol exposure is associated with adverse health effects on the developing fetus. Phosphatidylethanol (PEth) are specific direct biomarkers of alcohol that can be detected in human blood.The aim. To carry out a comparative assessment of the informative value of quantitative determination of phosphatidylethanol homologues 16:0/16:0, 18:1/18:1, 16:0/18:1 in the blood plasma of pregnant women at different gestation periods.Materials and methods. The longitudinal cohort study involved 126 pregnant women. Direct biomarkers of alcohol PEth were quantified in blood plasma at different gestation periods 16:0/16:0, 18:1/18:1, 16:0/18:1 by the LCMS method. Depending on the concentration of 16:0/18:1PEth, groups of women who consume different doses of alcohol were identified: 1st – PEth 8 ng/ml (non-drinkers), 2nd – PEth from 8 to 45 ng/ ml (drinkers of less than 1 dose), 3rd – PEth from 45 to 127 ng/ml (drinkers of more than 1 dose), 4th – PEth > 127 ng/ml (drinkers of significantly more than 1 dose).Results.Signifi antdiff encesinPEthconcentrationswererevealeddependingonthegestation period for the 18:1/18:1 marker (χ2 = 19.296; d.f. = 3; p = 0.001). At the fourth visit, which corresponds to 38-40 weeks of gestation, the PEth concentration of 18:1/18:1 was signifi antly lower than at the fi (T = 3.54; p = 0.0004), second (T = 2.06; p = 0.0395) and third visits (T = 2.21; p = 0.0269). The presence of only three high positive correlations is shown: between PEth markers 16:0/16:0 and 16:0/18:1 in the 1st group of women on the fi visit (ρ = 0.71) and in the 3rd group on the fourth visit (ρ = 0.72); between the PEth markers 18:1/18:1 and 16:0/18:1P in the 3rd group on the fi visit (ρ = 0.79). It was found that the range of PEth biomarker levels is 16:0/16:0 and 18:1/18:1 vary widely and overlap, there are no patterns in identifying maximum values depending on the dose of alcohol consumed, and there are no clearly traceable, unidirectional correlations in the concentrations of the three studied metabolites.Conclusion. Determination of the concentration of markers  PEth  16:0/16:0 and 18:1/18:1 in blood cannot be used to establish the fact of alcohol intake. While determining the concentration of the 16:0/18:1 PEth marker allows you to establish the fact and dose of alcohol consumed, which makes its use a universal screening tool.